End-of-life experiences of mothers with advanced cancer: perspectives of widowed fathers. Issue 4 (18th December 2015) - Park, Eliza M; Deal, Allison M; Yopp, Justin M; Edwards, Teresa P; Wilson, Douglas J; Hanson, Laura C; Rosenstein, Donald L
Abstract : Objective: Despite the importance of parenting-related responsibilities for adult patients with terminal illnesses who have dependent children, little is known about the psychological concerns of dying parents and their families at the end of life (EOL). The aim of this study was to elicit widowed fathers' perspectives on how parental status may have influenced the EOL experiences of mothers with advanced cancer. Subjects: 344 men identified themselves through an open-access educational website as widowed fathers who had lost a spouse to cancer and were raising dependent children. Methods: Participants completed a web-based survey about their wife's EOL experience and cancer history, and their own depression (Center for Epidemiologic Studies Depression Scale, CES-D) and bereavement (Texas Revised Inventory of Grief, TRIG) symptoms. Descriptive statistics, Fisher's exact tests, and linear regression modelling were used to evaluate relationships between variables. Results: According to fathers, 38% of mothers had not said goodbye to their children before death and 26% were not at all 'at peace with dying.' Ninety per cent of widowed fathers reported that their spouse was worried about the strain on their children at the EOL. Fathers who reported clearer prognostic communication between wife and physician had lower CES-D and TRIG scores. Conclusions: To improve EOL care for seriously ill patients and their families, we must understand the concerns of parents with dependent children. These data underscore the importance of parenting-related worries in this population and the need for additional clinical and research programmes devoted to addressing these issues.